Building an open and stable capital market: a supervision intensity perspective. Issue 3 (26th July 2022) - Fu, Fanjie; Collins, Alan; Yao, Shujie
Abstract: This article investigates the impact of supervision intensity on stock price crash risk (SPCR) in China. A firm's decision to hide bad news lies in the trade-off between the benefits of violation and the costs of being punished by government regulations. Our research findings reveal an inverted U-shaped relationship between SPCR and supervision intensity. Institutional shareholding strengthens the inverted U-shaped relationship between supervision intensity and SPCR through the mediating effect. This inverted U-shaped relationship is even more sensitive in low transparency firms. Better local market conditions and external auditing seemingly enhance supervision effectiveness, and hence mitigate SPCR. This article also discusses the supervision of other developed countries, such as the USA, Japan, and the UK, as well as other historical evidence to further inform the design of open and stable capital markets, particularly in the Chinese context.